Reduplikasi pada Tembang Dolanan Jawa - Ayuanda, Winda; Nasution, Khairina; Deliana, Deliana; Widayati, Dwi (Aksara: Jurnal Bahasa dan Sastra, 2024)
The culture of politeness adopted by the Javanese ethnic group means that the people often use indirect conversation to convey certain intentions. One of the roles of tembang dolanan is as a tool to convey ideas in the form of moral messages, since tembang dolanan contains good messages for life. So, studying Javanese, especially the reduplication process in dolanan songs, is important. The purpose of this analysis is to represent the forms and meanings that are often found in tembang dolanan, so that it can show the distinctive characteristics of the text/lyrics of tembang dolanan. This research was conducted using a qualitative descriptive research method, namely to describe the forms of reduplications, and to analyze the meaning contained in reduplication qualitatively. Research data collection was carried out by repeatedly reading, listening, and taking notes. The data was analyzed using the concept of reduplication in Javanese by Wijana (2021). From the research results it was found that the most widely used type of reduplication was full reduplication with 29 occurrences. Meanwhile, regarding the type of meaning, the emergence of the meaning of continuity dominates 25 times in the tembang dolanan. Keywords: reduplication, Javanese, tembang dolanan, meaning, morphology